2022
DOI: 10.3174/ajnr.a7738
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Vertebral Artery Hypoplasia with Posterior Circulation Stroke and the Functional Outcome of Patients with Atrial Fibrillation–Related Cardioembolic Stroke

Abstract: BACKGROUND AND PURPOSE:A cardiogenic embolus could reach the posterior circulation through the right vertebral artery because of a relatively larger diameter in cases of left vertebral artery hypoplasia. Hence, we investigated whether left vertebral artery hypoplasia is associated with cardiac embolisms with atrial fibrillation in the posterior circulation and its functional outcomes. MATERIALS AND METHODS:In this monocentric retrospective study, patients with acute cardioembolic stroke with atrial fibrillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Nonetheless, it is believed that BAH predisposes patients to atherosclerosis in the PC, ultimately causing ischemia in this system. 9,30 A more detailed analysis revealed that fetal origin was evident in almost 60% of the patients, with complete unilateral origin on the right side being the most common type observed, accounting for nearly 25% of the cases. Other types were observed in less than 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is believed that BAH predisposes patients to atherosclerosis in the PC, ultimately causing ischemia in this system. 9,30 A more detailed analysis revealed that fetal origin was evident in almost 60% of the patients, with complete unilateral origin on the right side being the most common type observed, accounting for nearly 25% of the cases. Other types were observed in less than 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that BAH is associated with PC stroke; however, no exact explanation has been offered. Nonetheless, it is believed that BAH predisposes patients to atherosclerosis in the PC, ultimately causing ischemia in this system 9,30 …”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that cerebral artery hypoplasia may be considered as an additional risk factor to the conventional vascular risk factors for subtle brain ischemia, symptomatic complaints, and recurrent stroke. 3,4,12 Cerebral artery hypoplasia was hypothesized either independently or in association with cardiovascular risk factors to produce clinical symptoms. Decreased vessel lumen may independently produce regional hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…While VAH was firstly considered as a non-dangerous anatomic variant, recent studies have associated its presence with increased predisposition for posterior circulation stroke, especially involving the posterior inferior cerebellar artery and lateral medullary infarcts, and when accompanied with other atherosclerotic risk factors. [2][3][4] Unilateral VAH may be associated with ipsilateral atherosclerosis of VA, relative hypoperfusion in ipsilateral PICA, and increased risk of contralateral cardioemboli whereas bilateral VAH may present with the involvement of multiple bilateral vascular teritories. 4 The most common types of anatomical variation in the circle of Willis includes hypoplasia of one or both of posterior communicating arteries (34-68%), hypoplasia of A1 segment of anterior cerebral artery (4-10%), absence of anterior communicating artery (12-21%), persistent fetal origin of posterior cerebral artery (4-26%), and infundibular dilatation of posterior communicating artery (7-15%).…”
mentioning
confidence: 99%
See 1 more Smart Citation